Anatomical considerations and clinical interpretation of the 12-lead ECG in the prone position: a prospective multicentre study. Issue 1 (5th October 2022) - Romero, Jorge; Garcia, Mario; Diaz, Juan Carlos; Gabr, Mohamed; Rodriguez-Taveras, Joan; Braunstein, Eric D; Purkayastha, Sutopa; Gamero, Maria T; Alviz, Isabella; Marín, Jorge; Aristizábal, Julián; Reynbakh, Olga; et al.
Abstract: Aims: The aim of this study is to provide guidance for the clinical interpretation of electrocardiograms (ECGs) in prone position and to establish the electroanatomic explanations for the possible differences to supine position ECGs that may be observed. Additionally, to determine if prone back ECG can be used as an alternative to standard ECG in patients who may benefit from prone position. Methods and results: The ECG in supine (standard ECG), prone back (precordial leads placed on the patient's back), and prone anterior position (precordial leads placed in the standard position with the subjects in prone position) were prospectively examined on 85 subjects. Comparisons of ECG parameters between these positions were performed. Computed tomography (CT) scans were performed in both positions to determine possible electroanatomic aetiologies for prone-associated ECG changes. There were significant differences in QRS amplitude in Leads V1–V5 between supine and prone positions. Q waves were more frequently observed in prone back position vs. supine position (V1: 74.1 vs. 10.6%, P < 0.0001; V2: 23.5 vs. 0%, P < 0.0001, respectively). Flat and inverted T waves were more common in prone back leads (V1: 98 vs. 66%, P < 0.0001; V2: 96 vs. 8%, P < 0.0001; V3: 45 vs. 7%, P < 0.0001). The 3D-CT reconstructions measurements corroborated the significant inverse correlation between QRS amplitude and the distance from the centre of the heart to the estimated lead positions. Conclusion: In prone back position ECG, low QRS amplitude should not be misinterpreted as low voltage conditions, neither should Q waves and abnormal T waves are considered anteroseptal myocardial infarction. These changes can be explained by an increased impedance (due to interposing lung tissue) and by the increased distance between the electrodes to the centre of the heart.